Property enhancement of recycled coarse aggregate using bio-treatment approach. (2021) - M., Deva Kumar; K.B., Anand; V., Poornima; Gopal, Murali; Gupta, Alka
Abstract: As the demand for concrete increases in the construction industry, it puts stress on nature due to the extraction of resources. The coarse aggregate is the component, which occupies around ¾th volume in concrete. The use of recycled coarse aggregates (RCA) is not very common due to the presence of porous old mortar attached around the surface of the aggregate. This makes the aggregates highly water absorbent in nature and also weakens the interfacial transition zone (ITZ). In this study, an attempt has been made to improve the properties of RCA through CaCO3 precipitation using Bacillus megaterium. The bio-deposition treatment yielded satisfactory improvement in the properties of RCA by filling of surface pores through precipitation. Reduction in water absorption and improvement in mechanical properties are derived. Microstructure studies also confirm the presence of CaCO3 through precipitation.